2017
DOI: 10.1007/s13320-017-0376-6
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol sensing over O+E+S+C+L+U transmission band based on porous cored octagonal photonic crystal fiber

Abstract: Abstract:A micro structure porous cored octagonal photonic crystal fiber (P-OPCF) has been proposed to sense aqueous analysts (alcohol series) over a wavelength range of 0.80 m to 2.0 m. By implementing a full vectorial finite element method (FEM), the numerical simulation on the proposed O-PCF has been analyzed. Numerical investigation shows that high sensitivity can be gained by changing the structural parameters. The obtained result shows the sensitivities of 66.78%, 67.66%, 68.34%, 68.72%, and 69.09%, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(15 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…It was found that the birefringence is sensitive to the varying frequency. It was seen that the birefringence is about 1.91 × 10 −3 at the frequency of 1.2 THz, which is comparable to previous reports [ 16 , 68 , 73 , 77 ]. The high birefringence of the sensor can be obtained by introducing asymmetric defects such as a porous core.…”
Section: Simulation Results and Analysessupporting
confidence: 88%
See 2 more Smart Citations
“…It was found that the birefringence is sensitive to the varying frequency. It was seen that the birefringence is about 1.91 × 10 −3 at the frequency of 1.2 THz, which is comparable to previous reports [ 16 , 68 , 73 , 77 ]. The high birefringence of the sensor can be obtained by introducing asymmetric defects such as a porous core.…”
Section: Simulation Results and Analysessupporting
confidence: 88%
“…Moreover, from the results, the effective mode area is 1.65 × 10 5 μm 2 , and the numerical aperture is about 0.33 at 1.2 THz. However, most previously designed sensors ignored the effective mode area [ 69 , 70 , 76 , 77 , 78 , 79 , 80 , 81 ] and numerical aperture [ 10 , 71 , 72 , 73 , 74 , 75 , 76 , 78 , 79 , 80 , 81 ] of the PCF.…”
Section: Simulation Results and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…) − ∂ L ∂r j = 0, where, r j = T, C, t p , and φ. We now introduce the perturbed vibrational procedure to solve equation (2) with small but finite value of G. Since the GNLSE contains perturbation terms, therefore, the modified Euler-Lagrange equations can be written as,…”
Section: Modified Nonlinear Schrödinger Equationmentioning
confidence: 99%
“…In addition, they showed and picked up the NA of 0.36 for U-band. In 2017, same authors enhanced the sensitivity of 1.06 times for identification liquor from drinks [28]. However, they didn't demonstrate the other pivotal parameters.…”
Section: Introductionmentioning
confidence: 97%